Structural analysis of an ergonomic motorcycle test rig using finite element analysis (FEA) / Muhammad Firdaus Azhar - Azhar, Muhammad Firdaus (2014)
As part of an effort to reduce global issue concerning motorcycle accidents, an ergonomic motorcycle test rig named Postura Motergo was established. In validating the test rig’s design, structural analyses were performed for blue print approval prior to fabrication. Computer Aided Design (CAD) model of the test rig was analyzed using Generative Structural Analysis (GSA) package in the state-of-the-art CATIA V5R20 software. Parameters considered were weight of a motorcyclist and material used as test rig structure as input to the Finite Element model. From there, the design was detailed out by the test rig’s design team before coming out with a final detail design which was also analyzed using FEA simulations. Tetrahedron mesh was used to generate the meshes on the finite element model. Boundary conditions were located at every area that was assumed to have zero degree of freedom (DOF) in real condition. The loading applied was 150kg taking a maximum average weight of a motorcyclist. Results showed that the test rig’s Von Mises Stress value was 1.79 x 108 MPa when 150kg of weight was applied. The yield strength of mild steel is 2.00 x 108 MPa and the factor of safety obtained was 1.12. With the positive results obtained from the FEA simulations, the Postura Motergo got its approval to be fabricated and safe to be used for further motorcycle ergonomic researchers especially the Motorcycle Engineering Test Lab (METAL) researchers. Upon the completion of development of the Postura Motergo, its first debut to the public during the Invention, Innovation and Design Exposition 2014 (IIDEX 2014) managed to secure a Bronze medal under the Invention category. Apart from that, two academic research papers relating to the Postura Motergo’s test rig were also accepted to be presented in two International Ergonomics Conferences.